A Binary Oppositions in Atia Abawi’s A Land of Permanent Goodbyes - Ghazali, Meka Mona; Oktafiyani, Elve (Muslim English Literature, 2025)
This research explores the binary opposition between the East and the West in A Land of Permanent Goodbyes and analyzes how these oppositions reinforce Edward W. Said's Orientalism. The method of the research is using a qualitative descriptive method by identifying, interpreting, and describing specific passages from the novel to examine the depiction of Muslim identity in the limited frame of Western perceptions. Said’s theory serves as the theoretical framework for this research. The findings reveal that the binary opposition between the East and the West creates stereotypes in which the East, often associated with Islam, is portrayed as inferior, while the West is depicted as superior to maintain white supremacy. This aligns with Said’s argument that Orientalist discourse creates a biased understanding of the East, positioning the West as the standard against which the East and, by extension, Islam are measured in old-fashioned ways. As a result, the narrator appears to adopt an Orientalist viewpoint, representing Islamic traditions as backward while portraying the West as a symbol of rationality and progress to maintain colonial manners. Such representations lead to a perception in which the Islamic world is seen as falling behind the West in terms of both culture and civilization. These stereotypes, rooted in Orientalism, also affect how Muslims view themselves in Western society.